Reliable Routing Protocol for Delay Tolerant Networks - Rosas-Olivos, E; Hidalgo-Castillo, N (IEEE Computer Society, 2016)
On post disaster scenarios, communication infrastructure can be seriously compromised, generating intermittent or null Internet access. Delay Tolerant Networks (DTNs) are a promising communication mechanism able to deal with connection disruptions enabling communication for affected people. DTNs forward messages through untrusted devices, which have better probability to reach destination. However, they are susceptible to attacks where participants forge their metrics in order for them to appear as a better alternative to route messages, thus most traffic is attracted to them. This problem is known as the blackhole attack. In this work we propose a routing protocol that verifies participants interactions using the Guy Fawkes protocol for an encounter-based routing protocol which routes messages based on the interactions of nodes. We propose a transmission ticket in order to achieve accountability in the actions of nodes. Routing decisions are based on the past tickets collected by the nodes. Our protocol creates a more reliable routing path by preventing the creation of fake interactions, and therefore blackhole attacks. Results show that our protocol reduces the number of messages attracted by malicious peers performing a blackhole attack, maintaining good delivery rates and low overhead for different network scenarios. © 2015 IEEE.